Bibliometric Analysis of the Role of Libraries in Achieving Sustainable Development Goals (SDGs) in International Scientific Publications 2015 – 2023 - Restiana Restiana; Retno Syekti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The role of libraries in supporting the achievement of Sustainable Development Goals (SDGs) has become increasingly important as awareness of sustainability and the importance of access to information grows. Bibliometric analysis of international scientific publications can provide an overview of the themes, contexts, and journals that most frequently publish articles related to the role of libraries in SDGs. Data collection was carried out using the Publish or Perish software and the Google Scholar database, and Boolean logic was used with the keywords "Library AND Sustainable Development Goals" and "Library AND Sustainable Development". The search yielded 42 journal articles related to the topic. The results showed that the number of publications on the role of libraries in SDGs fluctuated each year from 2015-2023, with the highest number of publications in 2017, totaling 8 articles. The journals that most frequently published articles on the topic were the International Journal of Library Science and The International Federation of Library Association and Institution Journal, with 4 articles each. The mapping of themes related to the topic using VosViewer was divided into 22 clusters, while the mapping of contexts was divided into 12 contexts related to the research topic. Based on the results of this study, the role of libraries in SDGs should be further optimized through international scientific journal article publications so that sustainable development goals can be achieved through the role of libraries.